Answer:
8
Step-by-step explanation:
10x-2x=8x
60+4=64
8x=64
x=8
Answer:
y^3/(27 x^3)
Step-by-step explanation:
Simplify the following:
((3 x)/y)^(-3)
((3 x)/y)^(-3) = (y/(3 x))^3:
(y/(3 x))^3
Multiply each exponent in y/(3 x) by 3:
(y^3)/((3 x)^3)
Multiply each exponent in 3 x by 3:
y^3/(3^3 x^3)
3^3 = 3×3^2:
y^3/(3×3^2 x^3)
3^2 = 9:
y^3/(3×9 x^3)
3×9 = 27:
Answer: y^3/(27 x^3)
Answer:
you would give back $7.87. But if you add the $40.50 instead you would give them $8.05
Step-by-step explanation: